Trajectory analysis among African hominoids can provide insights into genetic and epigenetic influences during ontogeny. Issue 1 (3rd July 2018) - Turley, Kevin; Simons, Evan A.; Frost, Stephen R.
Abstract: Objectives: Prior examination of the ontogeny of Hominoid talo‐crural joint morphology using Singular Warp analysis suggested both a genetic and epigenetic signal during development. This question is examined using trajectory analysis and its implications for the Hominin fossil record explored. Materials and methods: Trajectory analysis was used to examine talo‐crural joint shape at different molar eruption stages during development among a cohort of 221 specimens of Homo sapiens, Gorilla gorilla, Pan troglodytes, and Pan paniscus . Trajectory length, angle, and shape were compared among species. Trajectories that showed a consistent pattern of shape change were predicted to show a genetic signal, while change in that pattern an epigenetic signal. Results: The trajectories of all four hominoid tali were consistent during M1‐M2 development, but there was a change in Pan paniscus alone at M2‐ M3 . The tibial trajectories were again consistent in M1‐M2 development, however, only Pan paniscus persisted in this trajectory at M2‐M3 while the other three changed. Discussion: Trajectory analysis demonstrated an epigenetic signal in Pan paniscus in the talus and among the other three hominoids in the tibia. Behavioral (epigenetic) changes may impact hominoid ankle shape in extant species. These changes may reflect differences in locomotor repertoire altering shape, as has been suggested in the Hominin fossil record. Further examination of closely related hominoid species may provide insights into potential behavioral influences in the rapid change and diversity of Hominin talo‐crural shape in the Plio‐pleistocene.